Sikap Manjing, Ajur, Ajer dalam Bahasa Naskah - Wulandari, Arsanti (Jayapangus Press, 2025)
The script is a work representing past cultures. A work is the production of a particularr period of time and space, including the language in which it is represented. The language of the work reflects the mindset of the society of its creator. The character of society will be reflected in the language it uses. As an old work, babad ngayogyakarta hb iv-v, the European war babad, it seems to describe it. The language used in the text shows how the javans received their foreign languages to be absorbed so subtly in the various ways presented in the work. Adjustments were made in various ways, without abandoning his text form so that the text character was preserved. It takes note of the template attached to the charge. The adjustment in language became one of the features of the Javanese people receiving foreign cultures. The Indonesian government is optimistic the rupiah will continue to strengthen to rp9,100 per dollar, he said. The Javanese community was open to other cultures, trying to blend not fight but absorb and eventually expressed with a culture that had already fused with its own. He said the rupiah would continue to strengthen to rp9,100 per dollar in the Jakarta interbank spot market on Tuesday. The acquisition of language signified the greatness of its creator's society with its openness without leaving its own cultural roots.